Identifikasi Kesulitan Guru di Kabupaten Gowa dalam Mengembangkan Bahan Ajar Digital - Andromeda Valentino Sinaga (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
The purpose of this research is to identify what are the obstacles for teachers in developing digital teaching materials. This research is descriptive qualitative research with a survey method. The data analysis technique uses quantitative data with a descriptive approach. Based on survey research conducted on 50 teachers in Gowa Regency, the results showed that 96% of teachers used student books and teacher books as teaching materials, 62% of teachers had developed their own teaching materials, by making them in ms. word and then converting them into pdf files, as many as 80% of teachers find it difficult to develop digital teaching materials. This data is reinforced by 70% of teachers who have never participated in workshops or training activities. The results of the data also show that there are obstacles faced by teachers, namely teachers find it difficult to spend time because they think that there are many teaching materials on the market (which are ready to use), are constrained by inadequate facilities and infrastructure, do not have qualified technological capabilities, feel complicated in developing teaching materials, takes time and money, and does not know how to develop digital teaching materials. From the results of this study, it can be seen that teachers, who are respondents in this study, still lack the awareness to improve their ability to master the technology so that they can develop digital teaching materials that can be used in learning according to their needs.